2016
DOI: 10.3390/nu8020066
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Food Rations and Supplements on Micronutrient Status by Trimester of Pregnancy: Cross-Sectional Studies in the Maela Refugee Camp in Thailand

Abstract: Micronutrient fortified flour (MFF), supplementary food rations and micronutrient (MN) supplements may prevent deficiencies among pregnant women. Objectives of cross-sectional surveys in 2004 (n = 533) and 2006 (n = 515) were to assess the impact of new food rations (flour, oil) and supplements on MN status by trimester of pregnancy in the Maela refugee camp. Hemoglobin, iron status, zinc, retinol, β-carotene and tryptophan decreased, while α-/γ-tocopherol and 5-methyltetrahydrofolate (5-MTHF) increased from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 43 publications
(48 reference statements)
0
18
0
1
Order By: Relevance
“…Data from these 2 surveys with regard to micronutrient status, but not neonatal outcomes, have been published (16, 27, 28). The first survey took place in June 2004, 1 mo before adding whole-wheat MFF in the refugee food basket in July 2004 ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data from these 2 surveys with regard to micronutrient status, but not neonatal outcomes, have been published (16, 27, 28). The first survey took place in June 2004, 1 mo before adding whole-wheat MFF in the refugee food basket in July 2004 ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…This category covered 8 studies 17,[20][21][22][23]25,27,28 which presented aspects related to social, cultural, political and economic difficulties of access to food in refugee detention centers, refugee camps and in settlement destination countries.…”
Section: Food Inequitymentioning
confidence: 99%
“…In study A16, it points out the need of supplementation of minerals, such as iron, in refugee camps in Thailand and the consumption reduction of traditionally cultural foods such as betel nut, a characteristic seed of Asia. In addition, it is important to point out that the participants of the study were assisted by humanitarian food donation programs, and some families still reported the raising of animals such as poultry, pigs and goats, as a way to obtain food diversity 27 .…”
Section: Food Inequitymentioning
confidence: 99%
See 2 more Smart Citations